Some statistical aspects of children with disabilities in Assam, India. (2018) - Kalita, Jumi
Analysis of data plays a very important role in describing a data set from various angles of interest. It digs out different characteristics intrinsic in the data set. This paper analyses the occurrences of disability in children for gender-wise distribution, rural-urban distribution, and probes any probable relationship of mothers' age with occurrence of disability among newborns. The influence of the parameters like birth-cry, birth-weight, mother's health during pregnancy and severe health problem of the children within a short period after the birth in determining the disability types are analysed through multinomial logistic regression. Analysis of data relating to children with disability may be useful in predicting disability and taking precautionary measures.